The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/978-3-030-56223-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Electric Network Frequency Based Audio Forensics Using Convolutional Neural Networks

Abstract: Digital media forensics can exploit the electric network frequency of audio signals to detect tampering. However, current electric network based audio forensic schemes are limited by their inability to obtain concurrent electric network frequency reference datasets from power grids. In addition, most forensic algorithms do not provide high detection precision in adverse signal-to-noise conditions.This chapter proposes an automated electric network frequency based audio forensic scheme that monitors abrupt muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The experimental results demonstrate that there is no proportional enhancement in the model's performance with an increase 14/19 …”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The experimental results demonstrate that there is no proportional enhancement in the model's performance with an increase 14/19 …”
mentioning
confidence: 89%
“…The study conducted experiments on audio data tampering detection by inserting with 1-second, 2-second, and 3-second segments, whose results showed the highest detection accuracy for 3-second insert tampering. Mao et al 19 proposed a two-dimensional convolutional neural network model for binary classification of original audio and tampered audio. Zeng et al 27 proposed an audio tampering detection method based on ENF phase sequence representation learning.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin and Kang [8] proposed a wavelet-filtered ENF signal to highlight the abnormal ENF variations and employed autoregressive coefficients to train the classifier under a supervised-learning framework. Mao et al [9] utilized the multiple ENF features as input eigenvectors to the convolutional neural networks for detecting spliced audio. Meng et al [4] used the spectral entropy method to determine the length of each syllable and calculated the variance of the background noise of each syllable, then judged whether there is an operation of the heterogeneous splicing tampering in the audio by comparing the similarities between the variance of the background noise of each syllable.…”
Section: Audio Splicing Detentionmentioning
confidence: 99%
“…However, when the signal-to-noise ratio between the spliced segments is close or even the same, the performance of the noise levels based audio splicing detection methods will decrease sharply. In addition, based on the fact that inserting an audio segment into another audio recording leads to anomalous variations of the electric network frequency (ENF) signal, several kinds of research [7][8][9] have shown that it is an efficient way to detect spliced audio via the analysis of ENF signal. Whereas due to legal restrictions, it is difficult to obtain concurrent reference datasets of power systems, which makes the ENF based audio splicing detection methods difficult to implement [10].…”
Section: Introductionmentioning
confidence: 99%